WEBINAR AS COMPUTER-SUPPORTED COLLABORATIVE LEARNING OF PUPILS AND TEACHERS OF SECONDARY SCHOOLS - Tsarenko, B.O. (Journal of Information Technologies in Education (ITE), 2011)
Didactic possibilities of webinar using for implementation collaborative learning are analyzed in the article. The definition of webinar is substantiated and functional peculiarities are considered. Practical tasks that must be solved during adopting of webinars in learning process of secondary schools are revealed.